Principios variacionales y soluciones numéricas en elasto-visco-plasticidad - Taroco, Edgar (1980)
In the first part of this work a viscoplastic model is studied and it is shown how the viscoplasticity theory can be used not only to model this behavior but also to model plasticity as well as creep. The mixed-initial boundary value problem in elasto/viscoplasticity is presented for the case of quasi-static iso- thermal process and infinitesimal deformations. Different variational formulations related to the above boundary value problan are also deduced. A numerical algorithm based on the Finit Element Method and the Euler's Method, for the spacial and time cretizations respectively is presented. The algorithm in then used to obtain approximate solutions in elasto-plasticity, secundary creep and elasto/ viscoplasticity problems.